EMOTIVE VERBS IN LINGUISTICS: A COMPARATIVE ANALYSIS OF UZBEK AND ENGLISH LANGUAGES - Kurvonbekov Manuchekhr Islomjon ugli (Web of Journals Publishing, 2025)
This article explores the role of emotive verbs in linguistic structures through a comparative analysis of Uzbek and English languages. Emotive verbs, which convey emotions and attitudes, vary in syntactic structure, semantic meaning, and pragmatic application across languages. Using a qualitative comparative approach, the study examines common emotive verbs, their syntactic organization, and cultural influences on their usage. The findings reveal that while English emotive verbs are often direct and frequently used in everyday speech, Uzbek emotive verbs tend to be more indirect and context-dependent due to cultural norms of politeness and collectivism. This research contributes to the study of cross-linguistic emotional expression and provides valuable insights into the interaction between language and culture.
Keywords: Emotions, emotional states, syntactic roles, semantic roles, semantic nuances, pragmatic usage.